673PDNab-paclitaxel (Nab) plus gemcitabine (G) is more effective than G alone in locally advanced, unresectable pancreatic cancer (LAUPC): The GAP trial, a GISCAD phase II comparative randomized trial. (1st October 2019) - Cascinu, S; Berardi, R; Bianco, R; Bilancia, D; Zaniboni, A; Ferrari, D; Mosconi, S; Spallanzani, A; Cavanna, L; Leo, S; Negri, F; Beretta, G D; et al.
Abstract: Background: The role of a combination therapy is defined in metastatic pancreatic cancer but not in LAUPC. Lacking dedicated randomized trials, evidence mostly comes from retrospective or phase II studies. G alone remains the standard option following a subgroup LAUPC analysis of a GERCOR/GISCAD trial (J Clin Oncol 2005). Methods: GAP is a multicentre, open-label, randomized, comparative phase II trial testing the efficacy of NabG vs G. Patients ≤75 years, PS 0-1, were randomized 1:1 to Nab/G (Nab 125 mg/mq plus G 1000 mg/mq on days 1, 8 and 15 every 28 days for 3 cycles) or G (same schedule and doses). Patients not progressing after 3 cycles had to receive capecitabine plus radiotherapy for 5 weeks. Disease progression rate (DPR) according to RECIST 1.1 after 3 cycles of chemotherapy is the primary endpoint. With 80% power in detecting a reduction of DPR from 40% to 20%, one-tailed alpha=0.05, 124 patients were required. Progression-free survival (PFS) is a secondary endpoint; with 109 events the study has 80% power, with one-tailed alpha=0.05, to detect a 0.62 hazard ratio of PFS. Results: 124 patients were enrolled in this trial (4 withdrew consent after randomization in the G arm). Most of the patients were PS 0 (65.8%), and women (56.7%). The study met its primary endpoint DPR, with a reduction from 45.6% with G to 25.4% with Nab/G. There was no unexpected toxicity. One patient died during treatment with G due to a stroke. Conclusions: NabG reduces the rate of LAUPC patients who progress after 3 cycles of chemotherapy compared with G, especially in terms of distant relapses, positively affecting PFS and overall survival. Nowadays it should be the therapeutic option in this setting. Clinical trial identification: NCT02043730; 2013-002973-23. Legal entity responsible for the study: Fondazione GISCAD (Gruppo Italiano per lo Studio dei Carcinomi dell'Apparato Digerente). Funding: Celgene. Disclosure: S. Cascinu: Honoraria (self), Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Lilly; Advisory / Consultancy, Travel / Accommodation / Expenses: Bayer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Servier; Advisory / Consultancy: Amgen; Research grant / Funding (self), Travel / Accommodation / Expenses: Celgene; Honoraria (self): Sanofi; Research grant / Funding (self): Eisai. R. Bianco: Advisory / Consultancy: Boehringer Ingelheim; Advisory / Consultancy: Italfarmaco; Advisory / Consultancy: AstraZeneca. D. Ferrari: Advisory / Consultancy: Merck Serono; Advisory / Consultancy: Bristol-Meyers Squibb; Travel / Accommodation / Expenses: Roche. L. Cavanna: Advisory / Consultancy: AstraZeneca; Advisory / Consultancy: Merck; Travel / Accommodation / Expenses: Pfizer; Travel / Accommodation / Expenses: Ipsen; Travel / Accommodation / Expenses: Celgene. G.D. Beretta: Research grant / Funding (institution), Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Ipsen; Travel / Accommodation / Expenses: Celgene; Travel / Accommodation / Expenses: Servier; Research grant / Funding (institution): Lilly; Research grant / Funding (institution): Taiho Pharmaceutical. A. Sobrero: Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Merck Serono; Advisory / Consultancy: Servier; Advisory / Consultancy, Speaker Bureau / Expert testimony: Sanofi; Advisory / Consultancy, Speaker Bureau / Expert testimony: Celgene; Advisory / Consultancy, Speaker Bureau / Expert testimony: Amgen; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Bayer; Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Takeda; Speaker Bureau / Expert testimony: Lilly; Speaker Bureau / Expert testimony: AstraZeneca; Speaker Bureau / Expert testimony: Bristol-Meyers Squibb. A. Morabito: Travel / Accommodation / Expenses: Roche; Travel / Accommodation / Expenses: Novartis; Travel / Accommodation / Expenses: Ipsen; Honoraria (self): Delphi Diagnostics; Honoraria (self): Servier; Research grant / Funding (institution): Celgene. M.C. Piccirillo: Advisory / Consultancy: Glaxo; Honoraria (self), Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Travel / Accommodation / Expenses: Bayer; Honoraria (self): MSD; Research grant / Funding (institution): Roche. All other authors have declared no conflicts of interest.